Development of Green Areas and Village Parks in The Coastal District of Langkat Hilir Langkat Regency - M. Syahputra Batubara; Abdi Sugiarto; Cut Nuraini (Equivalent : Journal of Economic, Accounting and Management, 2026)
The development of green areas and village parks in the coastal area of Langkat Hilir, Langkat Regency, plays an important role in improving environmental quality, community welfare, and local economic potential. This study uses a descriptive qualitative approach, with data collected through in-depth interviews, participatory observation, and documentation. Data analysis was conducted using interactive analysis techniques, including data reduction, data presentation, and conclusion drawing. The results show that the existing condition of green open spaces (GOS) and village parks in Langkat Hilir is still limited in terms of both area and supporting facilities. Several constraints were identified, including limited land availability, coastal environmental degradation, limited community participation, minimal development budgets, and a lack of coordination in spatial planning regulations. Effective strategies for developing green areas and village parks include community-based participatory planning, site selection and zoning based on ecological conditions, the use of local plants, integration with tourism potential and local economic activities, sustainable management, and the application of adaptive designs suited to coastal conditions. The implementation of these strategies is expected to improve environmental quality, strengthen social welfare, and encourage the local economy through the use of village parks as spaces for education, recreation, and creative economic activities.